Penerapan Teknik Self-Management Dalam Meningkatkan Motivasi Belajar Siswa Sma - Selvi (CV. SINAR HOWUHOWU, 2025)
This study aims to examine the effect of applying self-management techniques on the learning motivation of high school students. A quantitative approach was employed using a quasi-experimental design with a pretest-posttest control group model. The sample consisted of two eleventh-grade classes, each comprising 30 students, assigned as the experimental and control groups. The experimental group received self-management training over four weeks, covering study planning, time management, and self-evaluation strategies. Data were collected using a learning motivation questionnaire and analyzed using paired sample t-tests and independent sample t-tests. The results revealed a significant increase in learning motivation in the experimental group compared to the control group. These findings suggest that self-management techniques are effective in enhancing students' motivation to learn. This strategy may serve as an alternative learning approach to foster students’ independence and responsibility in the learning process.